IMPLEMENTASI MEDIASI DALAM PENYELESAIAN SENGKETA HARTA BERSAMA PASCA PERCERAIAN : (ANALISIS PUTUSAN NOMOR 203/PDT.G/2023/PA.SKH): Implementation Of Mediation In The Settlement Of Joint Marital Property Disputes After Divorce: An Analysis Of Decision Number 203/Pdt.G/2023/PA.Skh - Daulay, R. Fahmi Natigor; Ahwan, Ahwan (Ganec Swara, 2026)
This study examines the implementation of mediation in resolving post-divorce joint marital property disputes through an analysis of Decision No. 203/Pdt.G/2023/PA.Skh, which embodies a settlement agreement with distinctive features, namely the classification of land as separate property and buildings as joint marital property, as well as unequal distribution schemes of 50:50 and 90:10. The research focuses on two main issues: the legal standing of separating land and buildings within mediation agreements under Islamic law and the Compilation of Islamic Law (KHI), and the juridical analysis of judicial considerations in endorsing such agreements. Employing a normative-juridical approach with a case study method of the Sukoharjo Religious Court decision, the study finds that the separation of land and buildings is justifiable based on the principles of independent ownership in fiqh muʿāmalāt, the concept of ḥaqq al-qarār (right of use), and the doctrine of commingling of assets. Furthermore, the deviation from the 50:50 formula under Article 97 KHI can be legitimized through freedom of contract and the maxim prioritizing intent over form. However, limited substantive judicial reasoning highlights the need for standardized guidelines in affirming non-standard mediation agreements